Acrylates as a significant causes of allergic contact dermatitis – new sources of exposure - Kucharczyk, Monika; Słowik-Rylska, Małgorzata; Cyran-Stemplewska, Sylwia; Gieroń, Monika; Nowak-Starz, Grażyna; Kręcisz, Beata (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2021)
Acrylate monomers have a wide range of applications. Since the 1950s, many reports of occupational origin allergic contact dermatitis due to (meth)acrylate monomers have been published. During last decades, (meth)acrylate allergy has undergone an occupational shift from dentistry toward beauty industry and medical devices. The aim of the study was to conduct a literature review on acrylates as a cause of allergic contact dermatitis, current sources of exposure as well as identification of professional groups with an increased risk of this allergy and methods of effective prevention. Database review: Medline search (PubMed), Wiley Online Library and Web of Science base in years 1956–2019 using the following keywords: acrylates, manicurists, dentists, dental technicians, medical devices, occupational exposure, and allergic contact dermatitis. 204 346 articles containing the term ‘acrylates‘ have been found. They include 2 042‬ articles with the word ‘manicurists’, 169 919 – ‘dentists’, 218 236 – ‘dental technicians’, 2 427 418 – ‘medical devices’. Fifty-nine articles were chosen based on analysis of abstracts and full texts. In the past allergy to acrylates was mainly of occupational origin and dental technicians were the most often affected professional group. Since the long-lasting manicure has become popular, this problem concerns both manicurists and their customers. Moreover, the new significant trend is non-occupational allergic contact dermatitis caused by medical devices especially dedicated to diabetes patients.